Implementation of Digital Technology to Instill Character Values of the Alpha Generation in Kindergarten - Alfia Cintya Ningrum; Reni Pawestuti Ambari Sumanto (Indonesian Values and Character Education Journal, 2025)
This study is motivated by the challenges faced by the Alpha Generation in maintaining character values amid the rapid development of digital technology. Instilling character values has become crucial in shaping resilient, tolerant, and integrity-driven individuals in the 21st century. This study aims to analyze the implementation of digital technology in instilling character values in early childhood, referring to the Pancasila Student Profile Strengthening Project (Proyek Penguatan Profil Pelajar Pancasila, P5). A qualitative approach using a case study method was employed in this research. The subjects included principals and teachers of Groups A and B from five early childhood education institutions that met the criteria of technological ownership, high accreditation, and involvement in character education. Data were collected through observation, semi-structured interviews, and documentation, with data analysis following the Miles and Huberman model, namely data reduction, data display, and conclusion drawing. The results indicate that digital technology, using videos, images, animations, audio, and educational games, can effectively shape children’s character values, particularly in the dimensions of religiosity, independence, creativity, cooperation, and global diversity. The study concludes by emphasizing the importance of collaboration among teachers, principals, and parents, as well as the availability of technological infrastructure, in optimizing digital media as a fun and meaningful tool for instilling character in the Alpha Generation.